Large Scale Synthesis of Carbon Nanotubes from Liquefied Petroleum Gas on Fe/MgO and Fe-Ni/MgO - Patel, Harshad; Manocha, Lalit M.; Manocha, Satish (Nanoscience & Nanotechnology-Asia, 2012)
For ultimate commercialization of carbon nanotubes, a cheap catalyst, a simple and large scale synthesis method and a cheap carbon source are necessary for their preparation at low cost. Here, an alternative way of preparing multi walled carbon nanotubes (MWNTs) on a large scale with low cost using conventional hydrocarbon source i.e., liquefied petroleum gas as carbon precursor (LPG) is presented. MWNTs were synthesized using LPG as carbonaceous precursor on Fe and Ni based catalyst on MgO substrate through chemical vapor deposition route. Since LPG is very cheap and has wide reserves, the results suggest that effective catalyst systems will allow the preparation of CNTs with yield up to 58% at low cost. The low ID/IG ratios for Fe/MgO and Fe-Ni/MgO were 0.41 and 0.43 respectively. This shows that CNTs synthesized with this system not only have a good yield but also good crystallinity too. The use of MgO as support minimizes the formation of amorphous carbon as the main impurity and deters the metal particles from aggregating. In this paper, results have been presented on the systematic study for the optimization of several growth parameters. The influences of various parameters such as nature of catalyst-substrate, gas flow rates, influence of hydrogen were investigated. This paper also includes the characterization of these CNTs by scanning electron microscope (SEM), transmission electron microscope (TEM), Raman microscope, thermo gravimetric (TG) analyzer etc.
Keywords: Thermal Chemical Vapor Deposition